Association between pre-pregnancy maternal stress and small for gestational age: a population-based retrospective cohort study - Manman Chen; Qiongjie Zhou; Yuanyuan Li; Qu Lu; Anying Bai; Fangyi Ruan; Yandan Liu; Yu Jiang; Xiaotian Li (BMC Medicine)
Abstract Background Maternal stress is a potential factor affecting fetal growth, but it is unknown whether it directly affects fetal growth restriction. This study aims to investigate the association between pre-pregnancy maternal stress with small for gestational age (SGA). Methods This study used a population-based retrospective cohort analysis to examine the association between pre-pregnancy maternal stress and SGA in offspring. Data were extracted from the National Preconception Health Care Project (NPHCP), conducted between 2010 and 2012, which encompassed preconception health-related information from 572,989 individuals across various regions in China. Logistic regression models were used to assess the associations between pre-pregnancy maternal stress variables and the risk of SGA. In addition, Synthetic Minority Over-sampling Technique (SMOTE) and Propensity Scores (PS) methods were used to enhance the model’s ability to the associations between pre-pregnancy maternal stress and SGA. Results Pre-pregnancy maternal stress was significantly associated with an increased the risk of SGA in offspring (OR 1.35, 95% CI 1.20 to 1.51, P < 0.001). Stress related to life and economic factors notably increased the risk of SGA across different socio-economic conditions, whereas stress related to friends did not show a statistically significant association (P > 0.05). Specially, individuals with lower socio-economic status that characterized by below high school education levels (OR = 1.45, 95% CI: 1.23 to 1.70), farmer occupation (OR = 1.33, 95% CI: 1.15 to 1.55, P = 0.002), rural residence (OR = 1.38, 95% CI: 1.22 to 1.56, P < 0.001), and younger age (under 35 years: OR = 1.35, 95% CI: 1.20 to 1.52, P < 0.001) were more susceptible to pre-pregnancy maternal stress, increasing their risk of SGA. Conclusions Pre-pregnancy maternal stress was positively associated with an increased risk of SGA in offspring. Individuals with lower socio-economic status were more likely to experience pre-pregnancy maternal stress related to life and economic factors, which in turn contributed to a higher risk of SGA.